FREQUENCY OF NUCLEAR ABNORMALITIES IN BUCCAL CELLS OF ROAD CONSTRUCTION WORKERS IN ANAMBRA STATE, NIGERIA: NUCLEAR ABNORMALITIES IN ROAD CONSTRUCTION WORKERS - ONWUKWE OKECHUKWU STEVEN; ACHUKWU PU; OKWUOSA CN; AZUBUIKE NC; ENIKE CE; ONYEMELUKWE AO; NNEDU EB; IKEGWUONU IC (Innovare Journal of Life Sciences, 2019)
Objective: The objective of this study is to assess the frequency of nuclear damage in the buccal cells of road construction workers in Anambra state, Nigeria. Methods: In this study, the frequency of nuclear abnormalities – cells with micronuclei (CMN), total MN (TMN), binucleate (BN) cells, cells with nuclear bud, and karyorrhectic cells, in exfoliated buccal cells of 33 road construction workers and 33 control subjects consisting of healthy persons was evaluated. Demographic data and exposure characteristics of the participants were obtained using a structured questionnaire. Buccal smears were obtained from both cheeks for each participant. The smears were stained using papanicolaou staining technique. At least 1000 cells in each smear were assessed and scored. The frequency of nuclear abnormalities in both road construction workers and control subjects was then compared. Results: The results obtained show a significant increase in the frequency of CMN (p=0.005), TMN (p=0.008), and BN (p=0.006) in buccal cells of road construction workers compared with control subjects. Factors such as age, years in occupation, and work days per week, use of protective materials, on-going medication, smoking habit, and alcohol consumption did not significantly affect the frequency of nuclear abnormalities among the road construction workers. Conclusion: Road construction workers may be exposed to substances capable of inducing nuclear damage in buccal cells.